2016
DOI: 10.1038/ncomms10713
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the nuclear bile acid receptor FXR cause progressive familial intrahepatic cholestasis

Abstract: Neonatal cholestasis is a potentially life-threatening condition requiring prompt diagnosis. Mutations in several different genes can cause progressive familial intrahepatic cholestasis, but known genes cannot account for all familial cases. Here we report four individuals from two unrelated families with neonatal cholestasis and mutations in NR1H4, which encodes the farnesoid X receptor (FXR), a bile acid-activated nuclear hormone receptor that regulates bile acid metabolism. Clinical features of severe, pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
191
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 251 publications
(200 citation statements)
references
References 43 publications
6
191
0
3
Order By: Relevance
“…Four distinct observations led us to conclude that this was due to a direct activation of the complement and coagulation by FXR. In the first, we confirmed an earlier study indicating that GW4064 induces expression of fibrinogens in a human hepatocyte cell line, and extended it to several other components of the complement and coagulation pathways [35] . In the second, we noted that the results of genome-wide binding studies for FXR in mouse and human hepatocytes identified the complement and coagulation pathway as third on the list of targeted pathways [36] .…”
Section: Do Fxr and Pparα Regulate Secretion?supporting
confidence: 77%
See 1 more Smart Citation
“…Four distinct observations led us to conclude that this was due to a direct activation of the complement and coagulation by FXR. In the first, we confirmed an earlier study indicating that GW4064 induces expression of fibrinogens in a human hepatocyte cell line, and extended it to several other components of the complement and coagulation pathways [35] . In the second, we noted that the results of genome-wide binding studies for FXR in mouse and human hepatocytes identified the complement and coagulation pathway as third on the list of targeted pathways [36] .…”
Section: Do Fxr and Pparα Regulate Secretion?supporting
confidence: 77%
“…We identified 4 patients from 2 families with loss of function mutations in the Kim NR1H4 gene, which encodes FXR [35] . These patients all exhibited severe neonatal cholestasis, with 2 in one family surviving after liver transplants and the other 2 dying prior to a year of age.…”
Section: Do Fxr and Pparα Regulate Secretion?mentioning
confidence: 99%
“…Hereditary cholestasis with conjugated hyperbilirubinemia in children presents as a range of disorders, from transient neonatal cholestasis (TNC) through benign recurrent intrahepatic cholestasis (BRIC) to progressive familial intrahepatic cholestasis (PFIC) . Of children with such cholestasis and low or normal serum gamma‐glutamyltransferase (GGT) activity (GGT <100 IU/L; “low‐GGT cholestasis”), two thirds carry either ATP8B1 or ABCB11 mutations; the remaining instances of childhood cholestasis with conjugated hyperbilirubinemia and low GGT can sometimes be attributed to mutations in TJP2 , which encodes tight junction protein 2 (TJP2); in genes involved in bile acid synthesis, including HSD3B7 , AKR1D1 , CYP7B1 , AMACR , and CYP27A1 ; in VPS33B and VIPAS39 , which cause arthrogryposis‐renal dysfunction‐cholestasis (ARC) syndrome; and in NR1H4 , encoding the nuclear farnesoid X receptor (FXR) (see http://onlinelibrary.wiley.com/doi/10.1002/hep.29020/suppinfo). However, approximately one fifth of such patients remain without an identified genetic defect, suggesting that mutations at additional loci are responsible for childhood low‐GGT cholestasis.…”
mentioning
confidence: 99%
“…FXR is known to tightly regulate bile acid, glucose and fat homeostasis through the gut-liver axis to ensure efficient functioning of both organs. Indeed, infants with mutations in FXR develop NASH and NAFLD with lipid deposition and bile acid accumulation [53] .…”
Section: Short Bowel Syndromementioning
confidence: 99%